THE TERM “CONCEPT” IN COGNITIVE LINGUISTICS THEORETICAL VIEWS ON ITS APPLICATION - Kholdorova , Nozima Akhmadjon kizi; Solijonov, Mukhammadjon (Educational Research in Universal Sciences, 2023)
The purpose of the article is to discuss and find out some features of lexical-semantic characteristics of using the term “concept”, “category”, and “frame” in cognitive linguistics.